1971
DOI: 10.1021/jo00816a024
|View full text |Cite
|
Sign up to set email alerts
|

Metal-catalyzed hydroperoxide reactions. II. Molybdenum-catalyzed epoxidations of styrene and some substituted styrenes

Abstract: Hewlett-Packard No. 2801A quartz digital thermometer. Temperatures are believed accurate to +0.04°.Kinetic measurements for all of the thenils, with the exception of 3,3'-benzo[b] thenil, 2,2'-benzo[b]thenil, and 5,5'-di(2"thienyl)-2,2'-thenil, were carried out in the same manner.A sample of the thenil, in the range of 2.5-3.0 mmol, was weighed to 0.1 mg and placed in a 250-ml Teflon screw cap bottle, along with a magnetic stirring bar. The thenil was dissolved in 100.0 ml of equilibrated dioxane with stirring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…which can be integrated to get [5] where C p = concentration of peroxyacetic acid, C u = concentration of undecylenic acid or its ester, M = the molar ratio C p,0 /C u,0 at t = 0, X u = (C u,0 − C u )/C u,0 = the fractional conversion of undecylenic acid or its ester. Plots of ln[(M − X u )/M(1 − X u )] against time were made at 25 and 35°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…which can be integrated to get [5] where C p = concentration of peroxyacetic acid, C u = concentration of undecylenic acid or its ester, M = the molar ratio C p,0 /C u,0 at t = 0, X u = (C u,0 − C u )/C u,0 = the fractional conversion of undecylenic acid or its ester. Plots of ln[(M − X u )/M(1 − X u )] against time were made at 25 and 35°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Published work has shown that epoxidation of α-β-unsaturated acids has found greater attention than the terminally unsaturated acids, such as undecylenic acid and its ester. Among the numerous approaches available for epoxidation, the processes involving organic peroxyacids and hydroperoxides, such as cumene hydroperoxide (CHP), t-butyl hydroperoxide (TBHP) and ethyl benzene hydroperoxide (EBHP), are by far the most important (5).…”
mentioning
confidence: 99%
“…However, peroxy acids are hazardous to handle and the yields obtained by using them in the epoxidation of some industrially relevant compounds such as α-olefins are poor. On the other hand, organic hydroperoxides such as cumene hydroperoxide (CHP), tert -butyl hydroperoxide (TBHP), ethylbenzene hydroperoxides (EBHP), etc. , possess many advantages, including relative ease of handling and their higher reactivities. Acid labile epoxides of such compounds as styrene, α-methylstyrene, α-pinene, etc.…”
Section: Introductionmentioning
confidence: 99%
“…9 There are contradictory reports about the basic mechanism, and two schools of thought have emerged. According to the general concept of PTC, various steps in this system are given Duncan et al, 4 have not given any direct structure of any of the species PW 4 , PW 3 , and PW 2 except the comment that these species are capable of coordinating with quaternary cation Q + . Further, in the case of PW 4 , it is expected that three of the tungsten sites remain seven-coordinated and the fourth does not, meaning that the latter must find a ligand in the reaction mixture to obtain coordinate saturation.…”
Section: Introductionmentioning
confidence: 99%